An Analysis of Tax Buoyancy Rates - Farooq Rasheed (Market Forces, 2006)
By using econometric techniques for estimating tax elasticities, this paper findssignificant but low tax buoyancy rates for GDP, M0 and volume of trade. Surprisingly,the theoretically important factor of tax evasion (SFTR) was found to be ineffective. Thisindicates that SFTR is not an adequate measure of tax evasion. There is no significantassociation between tax revenue growth and investment, credit, public debt and inflation.This illustrates the weakness of the tax regime in Pakistan.